KOMPETENSI MORAL DAN INTENSI WHISTLEBLOWING - Harti Budi yanti; Hasnawati Hasnawati; Christina Dwi Astuti; Haryo Kuncara (Media Riset Akuntansi, Auditing & Informasi, 2017)
This study examines the effect of age, gender and moral competence on whistleblowing intentions. Most of the respondents had a medium moral competence score. The older women group proved to be higher in moral competence scores than men of the same age. Age and gender do not affect whistle blowing intentions. However, moral competence strengthens the influence of age and gender on whistle blowing intentions. The results of this test provide support for human resource development practitioners to start paying attention to moral competence in addition to technical competence as the basis of consideration of recruitment, promotion and layoffs.